Keberadaan Ritel Modern dan Dampaknya terhadap Pasar Tradisional di DKI Jakarta - Hikmawati, Dianur; Nuryakin, Chaikal (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
This study aimed to analyze the impact of modern retail coexistence with traditional retail on traditional retail’s performance. Our observation is the 153 markets PD Pasar Jaya spread across DKI Jakarta and the modern retails (minimarkets, supermarkets, hypermarkets) location based on the retail zoning policy of Jakarta Regional Regulation No. 2/2002. This study used number of traditional retailers as a proxy of performance variable. The regression results indicate a non linear relationship between the number of modern retails–especially supermarket–and traditional retails performance in which the coexistence of one supermarket is positive for traditional market performance and negative afterwards.